Adapting traditional industries to national park management: A conceptual framework and insights from two Chinese cases. (20th September 2022) - He, Siyuan; Jiao, Wenjun
Abstract: The objective of this paper is to seek an eco-friendly development path for traditional industries in protected areas. We propose a conceptual framework that is built on the combination of ecological, multifunctional agriculture, and industrial integration literature. The framework provides a conceptual foundation for analysing the potential of traditional industry transformation in a single national park to improve rural livelihoods under conservation restraints. In a problem-oridented way, we conceptualise two transformation paths for traditional industries - the ecologicalisation of industry and the diversification of industrial functions – which aim to maintain and promote the stability of the social-ecological systems of national parks in general, and to enhance the added-value of traditional industries in specific. We apply our conceptualisation to two case studies in a comparative way to represent the feasibility of the framework to provide context-specific measures following the two paths. We identify and analyse key elements and conditions that are possible to transform the pastoralism in the Qilianshan National Park and tea cultivation in the Wuyishan National Park of China. Matching key elements to the conceptual framework, the results show that pastoralism needs to improve the branding of products and herders' capabilities of adjusting to the changing world; tea industries need to regulate branding, strengthen cooperation between producers of different scales, and promote cultural valorisation. Therefore, the regional industrial policies must coordinate with conservation policies to make sure rural communities realise their development rights while taking the responsibility of conservation. The theoretical contribution of this paper is that we conceptualise industrial development to be inclusive with conservation when economic development and conservation are thought incompatible. Our conceptual framework can be extended as a prescriptive management tool for integrated industrial planning and protected area management in China and other developing world. Highlights: Industrial development can be inclusive to livelihoods and conservation. Science-based value-adding is essential to traditional industrial transformation. An industrial transformation model is conceptualised for national park management. Traditional industry can contribute to the stability of social-ecological systems. Institution building and stakeholder cooperation are critical to the local context.